Features of autonomic cardiovascular control during cognition in major depressive disorder. (4th July 2020) - Bair, Angela; Marksteiner, Josef; Falch, Reingard; Ettinger, Ulrich; Reyes del Paso, Gustavo A.; Duschek, Stefan
Abstract: Previous research has suggested reduced parasympathetic cardiac regulation during cognitive activity in major depressive disorder (MDD). However, little is known about possible abnormalities in sympathetic control and cardiovascular reactivity. This study aimed to provide a comprehensive analysis of autonomic cardiovascular control in the context of executive functions in MDD. Thirty six MDD patients and 39 healthy controls participated. Parameters of sympathetic (pre‐ejection period, PEP) and parasympathetic control (high and low frequency heart rate variability, HF HRV, LF HRV; and baroreflex sensitivity, BRS) as well as RR interval were obtained at rest and during performance of executive function tasks (number‐letter task, n‐back task, continuous performance test, and Stroop task). Patients, as compared to controls, exhibited lower HF HRV and LF HRV during task execution and smaller shortenings in PEP and RR interval between baseline and tasks. They displayed longer reaction times during all conditions of the tasks and more omission errors and false alarms on the continuous performance test. In the total sample, on‐task HF HRV, LF HRV and BRS, and reactivity in HF HRV, LF HRV, and PEP, were positively associated with task performance. As performance reduction arose independent of executive function load of the tasks, the behavioral results reflect impairments in attention and processing speed rather than executive dysfunctions in MDD. Abnormalities in cardiovascular control during cognition in MDD appear to involve both divisions of the autonomic nervous system. Low tonic parasympathetic control and blunted sympathetic reactivity imply reduced physiological adjustment resources and, by extension, provide suboptimal conditions for cognitive performance. Abstract : This study investigated autonomic cardiovascular control during cognitive activity in MDD. In addition to impaired cognitive performance, patients showed reduced HRV, smaller decreases in pre‐ejection period and RR interval during task execution. On‐task HRV and reactivity in HRV, baroreflex sensitivity, and pre‐ejection period correlated positively with task performance. The study, for the first time, documented that that low tonic parasympathetic control and blunted sympathetic reactivity characterizing MDD may provide suboptimal conditions for cognitive performance.